EVALUASI IN VITRO TERHADAP KEMAMPUAN ISOLAT BAKTERI ASAM LAKTAT ASAL AIR SUSU IBU UNTUK MENGASIMILASI KOLESTEROL DAN MENDEKONJUGASI GARAM EMPEDU [In Vitro Evaluation of Cholesterol Assimilation and Bile Salt Deconjugation by Lactic Acid Bacteria Isolated - Lilis - Nuraida; Siti - Winarti; Hana - -; Endang - Prangdimurti (Jurnal Teknologi dan Industri Pangan, 2011)
Hypercholesterolemia is a risk factor for cardiovascular disease, the leading cause of death in many countries. Several studies have shown that reduction of excessive levels of cholesterol in the blood decreases the risk of cardiovascular disease. It is therefore important to develop ways of reducing serum cholesterol. Based on in vitro and in vivo studies, some of lactic acid bacteria (LAB) having potential probiotic properties can reduce total cholesterol and low-density lipoprotein cholesterol levels. The aim of this study was to evaluate the ability of LAB isolated from breast milk in reducing cholesterol by assimilation and by bile salt deconjugation activity in vitro.Thirteen strains of LABs were evaluated for their acid and bile salt resistance and selected to test their ability to assimilate cholesterol and to deconjugate bile salt (natrium taurocholate) in vitro. Cholesterol assimilation activity was determined by measuring the difference between the remaining cholesterol in broth medium inoculated with LAB with cholesterol in control after incubation. Bile salt deconjugation activity was determined by measuring free cholic acid released in broth medium after incubation with LAB. The results shows that most of the isolates was susceptible to low pH and all isolates used were able to survive in the presence of 0.5% bile salt. The LAB were also able to assimilate cholesterol at varying levels ranging from 0.86-14.97 µg/ml, with the highest activity showed by Pediococcus pentosaceus 1-A38, Pediococcus pentosaceus 2-B2 and Pediococcus pentosaceus 2-A16. Taurocholate deconjugation assay showed that the isolates have weak bile salts deconjugation activity as indicated by free cholic acid released ranging from 0.06-0.25 µmol/ml, with the highest release in Pediococcus pentosaceus 1-A38 and Pediococcus pentosaceus 1-A22. The present study suggest that Pediococcus pentosaceus 1-A38 was potential for the development of probiotic products with specific benefit to reduce cholesterol through cholesterol assimilation and deconjugation of bile salt.